2007
DOI: 10.1523/jneurosci.4630-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Modes of Synaptic Excitation of Olfactory Bulb Granule Cells

Abstract: Inhibition generated by granule cells, the most common GABAergic cell type in the olfactory bulb, plays a critical role in shaping the output of the olfactory bulb. However, relatively little is known about the synaptic mechanisms responsible for activating these interneurons in addition to the specialized dendrodendritic synapses located on distal dendrites. Using two-photon guided minimal stimulation in acute rat brain slices, we found that distal and proximal excitatory synapses onto granule cells are funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
195
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(202 citation statements)
references
References 54 publications
7
195
0
Order By: Relevance
“…There is a consensus that dendro-dendritic inhibition plays an important role in synchronization of the MCs (7,(17)(18)(19). However, the mechanisms for this synchronization are still controversial: the GCs are known to be able to spike and produce graded inhibition, and the roles of these two types of inhibition in synchronization are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a consensus that dendro-dendritic inhibition plays an important role in synchronization of the MCs (7,(17)(18)(19). However, the mechanisms for this synchronization are still controversial: the GCs are known to be able to spike and produce graded inhibition, and the roles of these two types of inhibition in synchronization are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…There may be several ways of amplifying the excitability of GCDs via neuromodulatory inputs to the external plexiform layer, which may underlie enhancement of gamma oscillations in different cognitive circumstances. A recent study showed that cholinergic drive from M1 receptors on GCDs enhances excitability of GCDs and elevates intracellular Ca 2ϩ (19).…”
Section: Discussionmentioning
confidence: 99%
“…S1 A and B) (4,25), and distal glutamatergic input synapses are colocalized with GABAergic output synapses in the distal domain with a 1:1 stoichiometry (7,24,26). PSD ϩ Cs in GCs were in tight apposition to the presynaptic marker bassoon in vivo (Fig.…”
Section: Development Of Glutamatergic Synaptic Input Sitesmentioning
confidence: 92%
“…It is possible that postnatal changes in the structure or function of axon terminals ending at GCs may result in different patterns of synaptic appearance in new GCs, and thus, could explain why axo-dendritic input does not develop before distal dendro-dendritic synapses in neonatal-generated GCs. However, axon terminals from the olfactory cortex ending at the GCs are already functional one week after birth (4,36), thus preceding the maturation of the neonatal-generated GCs that we studied. In addition, excitatory synapses in the proximal domain preceded those formed on the basal domain even though these two domains both receive axo-dendritic inputs.…”
Section: Influence Of Brain Maturation On Synapse Formation By New Nementioning
confidence: 97%
See 1 more Smart Citation